Stigma, Hopelessness, Depression and Associated Factors in People Living with HIV - Kılıçlı, Ayşegül; Akbulut, Şahide; Çakırca, Tuba Damar (My University, 2022)
Background: It was aimed to determine stigma, hopelessness, depression and associated factors in people living with HIV (PLWH).Materials and Methods: This descriptive cross-sectional study included 57 PLWH who admitted to Şanlıurfa Training and Research Hospital hospital between March 01-April 30, 2022. Berger HIV Stigma Scale, Beck Hope-lessness Scale and Beck Depression Inventory were filled during face-to-face interviews with patients.Results: It was determined Berger HIV-Stigma Scale mean score was high level (104.5±16.7), Beck Hopelessness Scale mean score was medium level (7.6±6.1) and Beck Depression Inventory mean score was medium level (16.3±13.7). Hopelessness rate was determined as 63.2% and depression rate as 40.4%. It was found a moder-ate correlation between stigma and hopelessness (r=0.44), a high level of correlation between stigma and depression (r=0.52), and a very high positive correlation between hopelessness and depression (r=0.80). Besides, a hopeless individual living with HIV was found to be odds 76 times more likely to be exposed to de-pression than a hopeful individual. In the regression analysis, it was determined that being single and growing up in a non-conservative family decreased HIV-stigma. On the other hand, it was observed that having to hide being infected with HIV increased HIV-stigma. It was determined that having to hide contagion with HIV de-creased hopelessness (odds=0.13) but depression increased hopelessness (odds=1.21). It was determined that hopelessness increased depression (odds=1.87).Conclusions: Stigma, hopelessness and depression are seen at high rates among PLWH and hopelessness in-creases depression significantly.
Keywords: Stigma; HIV; Depression; Hopelessness